Salivary cortisol and alpha-amylase levels during an assessment procedure correlate differently with risk-taking measures in male and female police recruits - Van Den Bos, Ruud; Taris, Ruben; Scheppink, Bianca; de Haan, Lydia; Verster, Joris (Frontiers in Behavioral Neuroscience, 2014)
Recent laboratory studies have shown that men display more risk-taking behaviour in decision-making tasks following stress, whilst women are more risk-aversive or become more task-focussed. In addition, these studies have shown that sex differences are related to levels of the stress hormone cortisol (indicative of activation of the hypothalamus-pituitary-adrenocortical-axis): the higher the levels of cortisol the more risk-taking behaviour is shown by men, whereas women generally display more risk-aversive or task-focussed behaviour following higher levels of cortisol. Here, we assessed whether such relationships hold outside the laboratory, correlating levels of cortisol obtained during a job-related assessment procedure with decision-making parameters in the Cambridge Gambling Task (CGT) in male and female police recruits. The CGT allows for discriminating different aspects of reward-based decision-making. In addition, we correlated levels of alpha-amylase (indicative for activation of the sympatho-adrenomedullary-axis) and decision-making parameters. In line with earlier studies men and women only differed in risk-adjustment in the CGT. Salivary cortisol levels correlated positively and strongly with risk-taking measures in men, which was significantly different from the weak negative correlation in women. In contrast, and less strongly so, salivary alpha-amylase levels correlated positively with risk-taking in women, which was significantly different from the weak negative correlation with risk-taking in men. Collectively, these data support and extend data of earlier studies indicating that risky decision-making in men and women is differently affected by stress hormones. The data are briefly discussed in relation to the effects of stress on gambling.